MODEL AKTAN GREIMAS DALAM NOVEL MENCARI PEREMPUAN YANG HILANG KARYA IMAD ZAKI - Erna Megawati (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2018)
The aim of this research is to discover the structure of fabula within the novel of Mencari Perempuan Yang Hilang. The method used in the research was narratology. Data is collected using library. Research is analyzed based on the theory of actantial model by Greimas. The result shows if the novel has six actants as suggested by Greimas which are subject, object, sender, receiver, helper, and opponent.